Pelaksanaan Pembuktian Dalam Tindak Pidana Terorisme - Juanrico Alfaromona Sumarezs Titahelu (JURNAL BELO, 2019)
Over the past few years these crimes have been growing more rapidly and disturbing the public. In the criminal acts of terrorism have become increasingly destructive form of crime with global scope. The Government has issued Government Regulation (decree) No. 1 of 2002 on Combating Criminal Acts of Terrorism. Then on April 4, 2003 decree that legalized as Law No. 15 Year 2003 on Eradication of Terrorism. But in reality proving criminal acts of terrorism is still a lot that is not in accordance with the existing rules, which means that there are many deviations that occur in the process of proving the criminal act of terrorism. Proving that in many criminal acts of terrorism against the rules of the higher law (Criminal Procedure Code) in comparison with the criminal act of terrorism law itself (Law No.15 of 2003). So that there are obstacles in proving the crime of terrorism is one of the Human Rights in value has been violating basic human